2022
DOI: 10.1177/00027642221118291
|View full text |Cite
|
Sign up to set email alerts
|

How Constructions of Interpersonal Responsibility Shape Undergraduate Student Networks in Times of Social Distancing

Abstract: Since Spring 2020, college students have experienced rapid and unpredictable shifts in their social and academic worlds. As institutions implemented social distancing policies, students had to navigate unstable norms related to peer interaction while negotiating what it meant to act responsibly to ensure their own safety and help their communities. Drawing on a network-based approach to pro-social behavior, we conducted a study of undergraduate students’ frequent interaction networks at one research university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The results showed that the stronger the sense of social responsibility, the more conducive it is to the construction of benign social relations as opposed to bad ones (Grebenshchikova, 2020;10.3389/fpsyg.202310.3389/fpsyg. .1117273 Paruzel et al, 2020Silva et al, 2021;Sorour et al, 2021;Blasco, 2022;Brown et al, 2022).…”
Section: Mediating Role Of Social Responsibility In the Relationship ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the stronger the sense of social responsibility, the more conducive it is to the construction of benign social relations as opposed to bad ones (Grebenshchikova, 2020;10.3389/fpsyg.202310.3389/fpsyg. .1117273 Paruzel et al, 2020Silva et al, 2021;Sorour et al, 2021;Blasco, 2022;Brown et al, 2022).…”
Section: Mediating Role Of Social Responsibility In the Relationship ...mentioning
confidence: 99%
“…Therefore, some scholars have used social identity theory to test the impact of social responsibility on all kinds of social relations. The results showed that the stronger the sense of social responsibility, the more conducive it is to the construction of benign social relations as opposed to bad ones ( Grebenshchikova, 2020 ; Paruzel et al, 2020 ; Silva et al, 2021 ; Sorour et al, 2021 ; Blasco, 2022 ; Brown et al, 2022 ).…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%